Abnormal interactions between context, memory structure, and mood in schizophrenia: An ERP investigation. (22nd July 2014) - Pinheiro, Ana P.; Del Re, Elisabetta; Nestor, Paul G.; Mezin, Jenna; Rezaii, Neguine; McCarley, Robert W.; Gonçalves, Óscar F.; Niznikiewicz, Margaret
Abstract This study used event‐related potentials to examine interactions between mood, sentence context, and semantic memory structure in schizophrenia. Seventeen male chronic schizophrenia and 15 healthy control subjects read sentence pairs after positive, negative, or neutral mood induction. Sentences ended with expected words (EW), within‐category violations (WCV), or between‐category violations (BCV). Across all moods, patients showed sensitivity to context indexed by reduced N400 to EW relative to both WCV and BCV. However, they did not show sensitivity to the semantic memory structure. N400 abnormalities were particularly enhanced under a negative mood in schizophrenia. These findings suggest abnormal interactions between mood, context processing, and connections within semantic memory in schizophrenia, and a specific role of negative mood in modulating semantic processes in this disease.